(Anti)racism on social media: an analysis of interactions from posts with afrofuturist contente - Klein, Geane Valesca da Cunha (2023)
In this study we provide an analytical description of the logic of interactions triggered by posts based on Afrofuturist content and disseminated on social networks, with the aim of analyzing how participants constructed subjectivities and how they discussed issues related to racism and anti-racism. The research adopted a hybrid methodology, combining bibliographical research and netnography (Kozinets, 2014) to understand its processes of signification, as well as the dialogic dynamics developed. Specific objectives included learning about Afrofuturism; apply concepts of dialogical analysis; identify participants’ roles; observe symmetries or asymmetries in the relationships developed; observe the chronotope of the statements and analyze the thematic-evaluative horizon. As a theoretical basis, concepts and discussions raised from the works of Bakhtin and Voloshinov were taken, especially Marxism and philosophy of language (1999) and Aesthetics of Verbal Creation (2003) and reverberated by Brait (2008), Stam (2000) and others . Furthermore, the study considered the perspective defined as Afrofuturism by Dery (1994) to discuss issues related to identity in the black body. Anchored in this socio-interactional view of language, the analysis highlighted the complexity of the self and the Other as interlocutors in a dialogical movement, revealing the capacity of dialogue for the construction and reconstruction of subjectivities